Optimising the recovery and stabilisation of intact oil bodies from oilseed rape - De Chirico, Simone (2019)
Oil bodies (oleosomes) are sub-cellular droplets representing the main form of energy storage in oleaginous plant seeds. The release of intact oil bodies by wet milling oilseeds results in a natural emulsion (no need for additional emulsifiers) and is likely to have a lower environmental impact than conventional oilseed processing. During the aqueous recovery of oil bodies, other water-soluble seed material is solubilised and carried-over in the final product. The aims presented in this thesis were: